2009
DOI: 10.1248/bpb.32.825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Claudin Expression on Paracellular Permeability, Migration and Invasion of Colonic Cancer Cells

Abstract: Tight junctions (TJs), the most apical intercellular structures in epithelial and endothelial cells, create a physiological intercellular barrier separating the apical and basolateral spaces, as well as regulating the paracellular permeability of various solutes. They also act as a divide between the apical and basolateral membranes, thereby maintaining cell polarity. TJs contain transmembrane proteins such as claudins, occludin and junctional adhesion molecules. The C-terminal regions of these proteins intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 40 publications
8
73
0
2
Order By: Relevance
“…Our data also show that claudin-4 overexpression increases the barrier function of TJs in gastric cancer cells, results that are consistent with previous studies in colon cancer 44 and MDCK cells, 45 thus, suggesting that overexpression of claudin-4 might suppress gastric cancer progression by enhancing the barrier function of TJs as well as by inhibiting cell migration and invasion.…”
Section: Bivalent Histone Modifications Are Associated With Cldn4 Repsupporting
confidence: 93%
“…Our data also show that claudin-4 overexpression increases the barrier function of TJs in gastric cancer cells, results that are consistent with previous studies in colon cancer 44 and MDCK cells, 45 thus, suggesting that overexpression of claudin-4 might suppress gastric cancer progression by enhancing the barrier function of TJs as well as by inhibiting cell migration and invasion.…”
Section: Bivalent Histone Modifications Are Associated With Cldn4 Repsupporting
confidence: 93%
“…The molecular mechanism involved in the internalization of CLAUDIN-1 into subcellular or nuclear compartments is hypothesized to be regulated by post-translational modifications like phosphorylation (D'Souza et al 2005), mutations (Dhawan et al 2005) and/or promoter gene hypermethylation (Boireau et al 2007). The increase in nuclear CLAUDIN-1 expression during scratch induction could reflect enhanced migration in close proximity of the scratch, because it has been suggested that CLAUDIN proteins translocate from the cell surface to intracellular compartments at the site where cell migration occurs (Takehara et al 2009). In our cell models, CLAUDIN-1 is already localized in the cell nucleus and only shows an enriched nuclear expression around the scratch in FTC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have described that claudin-1 or -4 proteins and mRNA levels were upregulated in colon cancer [11,[13][14][15]18]. In vitro, overexpression of claudin-1 and -4 specifically stimulates invasive activity of colon cancer cells with activation of matrix metalloproteinases [11,19]. Since such claudins are crucial components of tight junctions, alteration in their expression may affect cell proliferation, motility, and invasiveness in cancer cells in vitro, and in vivo loss of their expression contributes to a poorly differentiated phenotype as well as disease progression.…”
Section: Discussionmentioning
confidence: 99%